2017
DOI: 10.1128/jvi.00010-17
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus-Specific T Cell Receptor mRNA-Engineered Human T Cells: Impact of Antigen Specificity on Functional Properties

Abstract: Therapy with genetically modified autologous T cells has shown great promise in cancer therapy. For an efficient control of hepatitis C virus (HCV) infection, cytotoxic T cells (CTL) are pivotal, but persistence of activated T cells may lead to liver toxicity. Here, anti-HCV T cell receptors (TCRs) recognizing the HCV nonstructural (NS) NS3 or NS5 viral peptide target were examined by mRNA transfection of human peripheral blood lymphocytes (PBLs) derived from healthy donors as well as chronically infected HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Based on the TCR repertoire sequencing data, mRNA encoding the TCRs was synthesized and transfected into recipient effector T cells by electroporation. Gene optimization of TCR constant regions is done to prevent mispairing between the introduced and endogenous TCRs (26), and the TCR-redirected cells were used for analysis on day 1 post-transfection, as described (27).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the TCR repertoire sequencing data, mRNA encoding the TCRs was synthesized and transfected into recipient effector T cells by electroporation. Gene optimization of TCR constant regions is done to prevent mispairing between the introduced and endogenous TCRs (26), and the TCR-redirected cells were used for analysis on day 1 post-transfection, as described (27).…”
Section: Resultsmentioning
confidence: 99%
“…Characterized by strong cytolytic and proinflammatory cytokine responses, particularly in terms of IFN-γ production, they are noted of being of high-avidity and preferentially control the viral infection [62]. TCR redirection of human T cells toward these antigens renders them responsive to HCV-bearing hepatocytes and inhibits viral replication in vitro, proving their potential in TCR therapy [53][54][55]. In Soon et al [57], TCRs targeting epitopes at HEV RdRp and helicase domains were suggested as immunotherapeutics for immunosuppressed patients.…”
Section: Selection Of Viral Epitopesmentioning
confidence: 99%
“…Recent reports indicate that adoptive cell transfer currently comprised of TCR-engineered and chimeric Ag receptor (CAR)-T cells have the potential to treat a variety of other diseases including multiple sclerosis, inflammatory intestinal diseases and autoimmune diseases [97,98,99]. Moreover, in the last few years researchers have also considered extending T cell engineering to therapies for virus infections such as HIV-1, CMV, HBV, HCV and SARS [100,101,102,103,104,105,106,107]. In this regard, clinical evidence of the potential effectiveness of immune-modulatory strategies designed to strengthen HBV-specific T-cell responses by adoptive transfer of engineered antigen-specific T lymphocytes are based on the observation that virus-specific T cell administration through a bone marrow transplant from subjects who cleared HBV infection spontaneously, to patients with chronic HBV infection, led to virus control [108].…”
Section: Adoptive Transfer Of Genetically Engineered T Cellsmentioning
confidence: 99%
“…Similarly, liver transplantation in a patient with resolved HBV infection receiving a HBsAg positive graft resulted in viral clearance [109]. Thus, adoptive T-cell therapy using autologous T cells genetically engineered to express a canonical HLA class I restricted TCR, or a chimeric antigen receptor (CAR), targeting both HBV and HCV chronic viral infections has been attempted [103,104,105,106,107]. In HBV infection, the re-directed specificity of existing T cells by transfer of HBV-TCR genes has so far been tried in HBV transgenic mice and in patients with relapses of HBV-related HCC [110,111].…”
Section: Adoptive Transfer Of Genetically Engineered T Cellsmentioning
confidence: 99%